An ethics of responsibility and the origin of morality - Anton A. van Niekerk (Verbum et Ecclesia, 2023)
This article investigates the nature of an ‘Ethics of Responsibility’ (ER) as well as its significance for the broader research project dealt with, namely ‘Morality in History’. The article starts off with a conceptual analysis of the notions of ‘morality’ and ‘ethics’, followed by an exposition of Alasdair MacIntyre’s formulation of the ‘anomaly’ of current-day moral theory. This leads to a comprehensive analysis of MacIntyre’s argument as to why the Enlightenment project was, according to him, doomed to failure and a return to Aristotle is essentially called for. Consequently, the approach known as the ER is introduced, drawing on the work of Hans Jonas, Emmanuel Levinas, Richard Niehbur, Richard Bernstein, William Schweiker and Aristotle. The following concepts are analysed and integrated into the framework of the ER, namely accountability (Schwecker), reciprocity (Levinas), fallibility (Van Niekerk), futurity (Jonas), the dialectic between normativity and applications (Bernstein) and phronesis (Aristotle).